Association Between Times Spent on the Internet and Weight Status in Korean Adolescents - Seong-Ik Baek; Wi-Young So (Tehran University of Medical Sciences, 2011)
Background: This study investigates whether the amount of time that Korean adolescents spend on the Internet per day is related to their weight status.Methods: For this purpose, we analyzed data from the 2009 Korea Youth Risk Behavior Web-based Survey-V (KYRBWS-V), in which 72,399 students from the 7th to the 12th grade participated. We assessed the relationship between the amount of time spent on the Internet per day and body mass index (BMI) by using multivariate logistic regression analysis.Results: For boys, the odds ratio (OR; confidence interval (CI): 95%) between becoming overweight and the amount of time spent on the Internet per day was 1.225 (1.042-1.441; P=0.014) for >4 hour. The ORs (CI: 95%) between becoming obese and time spent on the Internet per day were 1.238 (1.096-1.399; P=0.001) for >2-≤3 hours, 1.208 (1.021-1.428; P=0.027) for >3-≤4 hours, and 1.303 (1.109-1.532; P=0.001) for >4 hours. For girls, the ORs (CI: 95%) between becoming overweight and time spent on the Internet per day were 1.265 (1.089-1.469; P=0.002) for >2-≤3 hours and 1.338 (1.080-1.659; P=0.008) for >3-≤4 hours. The ORs (CI: 95%) between becoming obese and amount of time spent on the Internet per day were 1.239 (1.014-1.513; P=0.036) for >2-≤3 hours and 1.541 (1.182-2.010; P=0.001) for >3-≤4 hours.Conclusion: Korean adolescents who spend more time on the Internet are predisposed to weight-related problems, regardless of age, time spent in physical exercise, mental stress, sleep duration, etc.